State’s Obligation to Protect Human Rights in Business Activities According to the Guiding Principles on Business and Human Rights: Implementing the United Nations Protect, Respect, and Remedy Framework - Recommendations for Vietnam - Ha, Le Thi Tuyet (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The state’s duty to protect human rights in corporate activities, as outlined in the UN Guiding Principles on Business and Human Rights (UNGP), is essential in promoting, respecting, and safeguarding human rights within the business sector. This article examines the state's obligations under the UNGP in the context of corporate activities. It connects this analysis with the development and application of a National Action Plan (NAP) based on the general provisions of the UNGP. Employing a qualitative research methodology, the study utilises a doctrinal approach to analyse international legal instruments, national policies, and academic literature related to the UNGP framework. Additionally, the article incorporates a comparative approach, reviewing examples of NAP implementation in various countries to provide practical insights for Vietnam. The findings emphasise aligning Vietnam's legal and policy frameworks with the UNGP to enhance corporate accountability and human rights protection. The study concludes with several actionable recommendations for Vietnam to implement the UNGP effectively, considering its unique socio-economic context and the demands of global development. These recommendations aim to strengthen Vietnam's capacity to address human rights challenges in corporate practices and contribute to its sustainable development goals.